A Narrative Review of SARS-CoV-2 Pathogenesis, Transmission, and Clinical Manifestations - Amin Sharifan (Mazandaran University of Medical Sciences, 2022)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has become a major global concern. As of writing this manuscript, there are over 224 million cases diagnosed, and 4.5 million recorded deaths with the Coronavirus Disease 2019 (COVID-19). Objectives: This article reviews the studies conducted on SARS-CoV-2 pathogenesis, transmission, and different clinical manifestations. Methods: An extensive online search was conducted on PubMed and Google Scholar search engines. The following keywords and their combinations were used to complete this review: "SARS-CoV-2", "COVID-19", "virology", "mechanism of action", "transmission", "clinical manifestations", "laboratory findings", and "comorbidities." Results: The SARS-CoV-2 spike glycoprotein recognizes the human angiotensin-converting enzyme 2 receptors, and through that, the virus can enter its host cell. The virus is mainly transmitted via respiratory and or airborne droplets. The severity of the COVID-19 clinical manifestations relies on the associated comorbidities and or old age, which ranges from little-to-no symptoms to severe and critical conditions. Fever, loss of appetite and or smell, fatigue, and dry cough are among the most reported symptoms. Underlying conditions may lead to severe or critical stages of COVID-19. Conclusion: The SARS-CoV-2 nucleocapsid and receptor-binding domain could be two potential targets for future vaccines and drugs. It appears that the virus is adapting to each region's specific environment; therefore, new endemic variants are forming.